The Role of Marine and Fishery Resources Supervision of Ternate in Handling Illegal Fishing - Hanafi, Muhammad Amin; Farid, Achmad Miftah; Pontoh, Pangeran Bintang Putra S; Konoras, Isyana Kurniasari (Dinasti Research, 2025)
The title of this paper is “The Role of Marine and Fishery Resources Supervision of Ternate in Handling Illegal Fishing”. The object of this research is the action to settle illegal fishing by Technical Implementation Unit for Marine and Fisheries Resources Supervision of Ternate. This paper aims to analyze the how this Technical Implementation Unit settles the illegal fishing crimes in Ternate as well as the factors that influence their actions in handling illegal fishing crimes in Ternate. This paper employed the sociological legal research method which studies and analyzes the legal behavior of individuals or communities, in relation to the law and the data sources used come from primary data. It employed the the conceptual approach, the statute approach, and the case approach. Results showed that the Technical Implementation Unit for Marine and Fisheries Resources Supervision of Ternate resolves illegal fishing crimes namely by carrying out supervision, outreach to fishermen, carrying out routine patrols, verification and validation and carrying out investigations. The factors that influence their actions include the lack of human resources infrastructure facilities and the failure to achieve targets